Female sexual function as a predictor of well-being - Starc, Andrej (Array, 2019)
Introduction: The purpose of this study was to evaluate the relationship between the WHO-5 Well-Being Index and variables from the Female Sexual Function Index (FSFI) in a large-scale sample of partnered and single women. Methods: Based on the Kolmogorov-Smirnov and Shapiro-Wilk test on six claims of FSFI, a non-parametric statistical analysis was used. Results: Statistical significance was set at p<0.05. The sample included 635 female participants, aged 18 to 89 years. There was a strong link between all the six FSFI claims with marital status and number of sexual partners. The group of women who were involved in sexual intercourse in the previous 4 weeks shows higher life satisfaction (n=366; 50-100%) compared to the group (n=37; 0-49%) who were not involved in sexual intercourse in the previous 4 weeks. Even though the frequency of sexual functioning according to FSFI scores did not differ between the two groups (χ2 (1)=0.101, p=0.750), they did differ in the quality of sexual experience. Conclusions: These results extend previous findings by confirming a strong relationship between sexual well-being and overall life satisfaction within individuals. They confirm the importance of sexual satisfaction in shaping the overall quality of life not only for men but also for women.